Comparative study of feeding practices among children less than two years attending rural and urban primary health centers, Mysuru, Karnataka - Lokesh, Nagendra; Kulkarni, Praveen; R., Pragadesh; Basheer, Sayana; D., Sunil Kumar; A., Vanmathi (International Journal Of Community Medicine And Public Health, 2023)
Background: Breastfeeding is considered one of the most significant aspects of a child’s health and survival. Breastfeeding is unquestionably the "GOLD STANDARD" dietary intake during the first six months after birth. So it is necessary to know about the feeding practices among children less than two years in both rural and urban areas. Aim of study was to compare the feeding practices among children less than two years attending the urban and rural Primary health centers under JSS Medical College, Mysuru. Methods: This analytical cross-sectional study was conducted among 280 mother and their children residing in both rural and urban areas of Mysuru for six months. A pretested structured questionnaire was used to collect the socio-demographic characteristics and feeding practices. Feeding practices among study subjects were analyzed using SPSS 23 software. Results: In the present study, 35% had poor, 57.1% had average and 7.9% had good infant and early child feeding practices in rural areas, on the other hand, 19.3% had poor, 55.0% had average and 25.7% had good in urban. In this study, the frequency of breastfeeding practices, pre-lacteal feeding, and overall feeding practices were significantly associated with place of residence. Conclusions: This study concludes that though pre-lacteal feeding and bottle feeding were more in urban areas, the overall feeding practices were poorer in rural than urban.